One in twenty : a study of homosexuality in men and women - Magee, Bryan (London, 1966)
When this study of homosex uality in men and women was first published over two years ago The Times Literary Supple ment said: 'The book expresses tolerance, understanding and even tenderness on the part of a writer who has no personal axe to grind'; and The Sunday Times called it 'a clear and extremely well-balanced account of most of the problems individuals and society have to face with regard to homosexuality'. Now the author has revised the book, bringing it completely up to date, in the light of the Homo sexual Law Reform Act of 1967.
Keywords: Sociology